Addressing the Inequities in Access to Reproductive Healthcare for Gay Male Couples - Wyont, Logan Matthew (Wake Forest University, 2018)
The current system of federalism in the United States that allows individual state control over reproductive healthcare laws creates a discriminatory impact for gay male couples based upon geographic location. Thus, gay male couples who seek to become parents whe re one of the intended fathers is biologically related to the child , may be unable to do so depending on the laws that govern reproductive technology in the state they live in. In order to remedy this blatant discrimination, the United States Supreme Court should extend the currently recognized constitutional right to reproduce. This extension would allow the current right to reproduce to encompass a negative right to access reproductive healthcare. The Supreme Court should declare that all United States ci tizens should be able to access the means necessary to reproduce regardless of their classification.
Keywords: Discrimination; Federalism; Gay Male Couples; Inequities; Law; Reproductive Healthcare